Recurrent Gastric Cancer Initially Presenting with Dysphagia induced by Idiopathic Inflammatory Myositis: A Case Report - Che-Hao Chang; Li-Chun Lu (Journal of Cancer Research and Practice)
We present the case of a 51-year-old female patient who was diagnosed with gastric cancer and subsequently underwent surgical resection, followed by adjuvant chemotherapy. Despite these interventions, the disease recurred, manifesting as laryngeal weakness and clinical features indicative of an autoimmune disorder. Further diagnostic evaluation confirmed the presence of a paraneoplastic autoimmune syndrome, specifically dermatomyositis with concomitant features of Sjögren’s syndrome. Notably, the patient also had dysphagia, a relatively rare manifestation in this clinical context. The optimal therapeutic approach for managing this paraneoplastic autoimmune condition remains to be investigated.